1994
DOI: 10.1152/jn.1994.72.3.1420
|View full text |Cite
|
Sign up to set email alerts
|

Many areas in the human brain respond to visual motion

Abstract: 1. The regions of the human brain responsive to motion were mapped using the H2(15)O position emission tomography (PET) activation technique and compared by viewing a moving random dot pattern with a stationary dot pattern. The stimulus was optimized in dot density and 3 degrees in diameter. 2. In addition to bilateral foci at the border between Brodmann areas 19 and 37, a V1/V2 focus and a focus in the cuneus reported earlier, we observed activations in other visual areas (lower BA 19 and the parieto-occipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
105
3
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(137 citation statements)
references
References 0 publications
27
105
3
1
Order By: Relevance
“…Previous human imaging studies often have reported a motionselective area in this general region of cortex (Watson et al, 1993;De Jong et al, 1994;Dupont et al, 1994;McC arthy et al, 1995;Shipp et al, 1995;Tootell et al, 1995a,b). Influenced by the macaque data, this human motion-selective area often has been attributed to human V3 De Jong et al, 1994;Dupont et al, 1994) (but see Tootell et al, 1995aTootell et al, ,b, 1996a.…”
Section: Motion Selectivity In Human V3a and V3mentioning
confidence: 94%
See 2 more Smart Citations
“…Previous human imaging studies often have reported a motionselective area in this general region of cortex (Watson et al, 1993;De Jong et al, 1994;Dupont et al, 1994;McC arthy et al, 1995;Shipp et al, 1995;Tootell et al, 1995a,b). Influenced by the macaque data, this human motion-selective area often has been attributed to human V3 De Jong et al, 1994;Dupont et al, 1994) (but see Tootell et al, 1995aTootell et al, ,b, 1996a.…”
Section: Motion Selectivity In Human V3a and V3mentioning
confidence: 94%
“…Influenced by the macaque data, this human motion-selective area often has been attributed to human V3 De Jong et al, 1994;Dupont et al, 1994) (but see Tootell et al, 1995aTootell et al, ,b, 1996a.…”
Section: Motion Selectivity In Human V3a and V3mentioning
confidence: 99%
See 1 more Smart Citation
“…One example is human MT(ϩ), which responds better to moving stimuli compared with stationary stimuli (Zeki et al, 1991;Dupont et al, 1994;Tootell et al, 1995b;Goebel et al, 1998;Sunaert et al, 1999). Several studies since distinguished between presumptive "MT" and "MST" in human "MTϩ," on the basis of differences in higher-order motion processing (Neri et al, 1998;Dukelow et al, 2001).…”
Section: Global Functional Mapsmentioning
confidence: 99%
“…Neurological patients whose cortical damage includes area V5 have de¢cits in perceiving motion which range from an almost total inability to perceive the movement of objects to de¢cits in second-order motion only (see, for example, Zihl et al (1983), Hess et al (1989), Baker et al (1991), Plant & Nakayama (1993) and Shipp et al (1994)). There are areas of cortex other than V5 involved in the analysis of motion (see, for example, Dupont et al (1994Dupont et al ( , 1997 and Orban et al (1995)), and lesions which do not include human area V5 can also lead to prominent impairments in aspects of motion perception (Vaina & Cowey 1996;Vaina et al 1998). Human areas V1, V2 and V3a, for example, are all activated by visual motion (McKeefry et al 1997), V3 by motion in depth (de Jong et al 1994), and V2 and V3a respond to illusory motion (Tootell et al 1995), although to a lesser extent than V5 (Tootell et al 1995).…”
Section: Introductionmentioning
confidence: 99%